ChemInform Abstract: Catalyst Controlled Divergent C4/C8 Site‐Selective C—H Arylation of Isoquinolones. Issue 51 (December 2015) - Lee, Soyoung; Mah, Shinmee; Hong, Sungwoo
Abstract: The Pd‐catalyzed arylation of isoquinolones (I) with aryliodonium salts leads to 4‐arylisoquinolones (III), whilst an Ir‐catalyzed reaction affords 8‐arylisoquinolones (V).